Netting of capacity in interconnector auctions - Felix Höffler; Tobias Wittmann (Max Planck Institute for Research on Collective Goods, 2006)
Scarce interconnector capacities are a severe obstacle to transregional competition and a unified market for electricity in the European Union. However, physically the interconnectors are rarely used up to capacity. This is due to the fact that the current allocation schemes make only limited use of the fact that currents in opposing directions cancel out. We propose a netting auction mechanism which makes use of this and in which even small transmission capacities can generate large competitive pressure in adjacent markets. Netting increases the usage of capacity and reduces the auctioneer's incentive to withhold capacity from the auction.
Keywords: L94; D44; 330; Divisible good auctions; interconnector; electricity marktes; competition policy; Stromnetz; Kapazitätsauslastung; Auktion; Elektrizität; Theorie; EU-Staaten